Curricula, Examinations, and Assessment in Secondary Education in Sub-Saharan Africa - World Bank (Washington, DC : World Bank, 2012)
Curriculum reforms first and foremost should focus on improving the current teaching and learning processes. As a systemic challenge, these changes need to include re-orientation from secondary education as pre-academic tertiary education to a wider range of options, including vocational education and the world of work. Curriculum reforms in Sub-Saharan Africa (SSA) require comprehensive approaches directed at the complexity of the educational system at large. It requires the acknowledgement of past obstacles and current challenges to reform, as well as the challenges additionally created by the reforms. Human and physical resources, perceptions, experiences with past reforms and current school and classroom practices determine the limits of what educational systems can absorb in terms of development. Many high political ambitions have implications that are beyond current context and conditions. It therefore makes sense to have realistic ambitions and scope of curriculum reform, because these may increase the potential for successful implementation. Sometimes, less could actually be more. It is recommended that curriculum reform and strategies be based on the realities on the ground and much less on political ambitions. Implementation of curricula depends on improved coordination of development efforts with a focus on curriculum. It is recommended to increase the efficiency, clearly define institutional responsibilities, and provide for better cooperation and communication with across existing institutions and departments.